Memory and Abalienation In the Work of Paula Meehan: Exploring Memory and Identity in Paula Meehan's Poetry (Journal of Advances and Scholarly Researches in Allied Education, 2011)
The personal and the political are entwined in thepoetry of Paula Meehan. It is a connection far exceeding any simple relationship between singular and collective perceptions, yielding instead to anenduring  engagement with the processesof bearing witness. If poetry is for Meehan “an act of resistance, an act ofsurvival,” it aptly demonstrates that with human  endurance must come an acknowledgment of thefragmentary and often in expressible self (O’Halloran and Maloy 7). Many of her poems—from the earliest workthrough to the recent Painting Rain (2009)—return to traumatic childhood inorder to explore the fraught attempts of the individual to find meaning in ahostile and confusing world. Memory is at the core of this exploration, notjust in providing significant material for the poet’s art, but in emphasizingthe continuing dynamic between present and past selves; a dynamic that relatesnot only to individual self-identity, but to how this is mediated in thecreation of larger communities and national groupings.